The role of probiotics in ameliorating hyperuricemia: a review - ZOU Yan, HUANG Enshan, ZHAO Dong, HUANG Lichun, SU Danting, ZHANG Ronghua (预防医学)
Hyperuricemia (HUA) is a metabolic disorder syndrome caused by purine metabolism dysregulation, and its prevalence increases year by year. The development and progression of HUA are accompanied by significant alterations in the composition of intestinal microbiota, making probiotics a potential and safe method to reduce serum uric acid. Probiotics ameliorate HUA through three pathways: competing with intestinal epithelial cells for purine absorption to decrease uric acid synthesis, inhibiting xanthine oxidase activity through modulation of inflammatory cytokines to reduce the conversion of purine to uric acid, as well as restoring and maintaining an orderly state of the gut microbiota to facilitate normal uric acid excretion. This article reviews the role of probiotics in ameliorating HUA, so as to provide the reference for the application of probiotics in the prevention and intervention of HUA.